PENGEMBANGAN DESIGN CHART SISTEM PONDASI ,PILED RAFT DI TANAH PASIR DENGAN PEMODELAN 2D AKSISIMETRIK DAN 3D - Ghalba, Ahrufan
ABSTRACT: Piled raft foundation is a pilegroup foundation in which the raft is also considered to carry the load, so that its number of piles can be reduced to obtain optimum capacity. Many researches have been conducted to measure the percentage of the load carried by raft, the results have been also presented in the form of design chart. From these researches it turns out that important parameters influencing the percentage of raft load are raft stiffness, pile stiffness, pile group spacing, pile slenderness, and overburden pressure at raft level. Hyperbolic soil models and hardening soil model for medium dense and dense sand are used in this thesis. While the piled raft modelled are 5x5 system. Computer modeling are using 2D axisymetric and 3D methods. The results confirms with laboratory test models for 3x3 piled raft system, that is the percentage of raft load is sufficiently high even at small settlement of the raft. The shape-ofpile load-transfer curves agrees-with-those of laboratory test results for single pile models. There is incompatibility however, between 2D axisymetric and 3D on the value ofpile end bearing, where 2D axisymetric model results in higher values. Comparison of settlement between 2D axisymetric and 3D results shows compatibility on center, settlements but incompatibility on differential settlements. Parameter tests of pile group spacing, pile slenderness, and overbuden pressure confirms the results of previous researches where increase in pile group spacing, decrease in pile slenderness and increase in overburden pressure, all would increase raft load percentage. While the increase in raft stiffness would also increase raft load percentage. The results for medium dense sand shows that 2D axisymetric and 3D models gives almost identical values of raft load percentage, while the results for dense sand gives different values. This is due to difference in computation of pile end bearing values. In layered soils models, the influence of pile end bearing is very significant, where pile group load percentage are greater if they rest on stiffer soils. The design charts for medium dense sand have been completed. Not so for dense sand due to contradictory results emerged Design chart can be used in aiding design for 5x5 piled raft system.